The Multiplier for Federal Spending in the States During the Great Depression. (13th March 2015) - Fishback, Price; Kachanovskaya, Valentina
Abstract : To estimate the impact of federal spending on state incomes, we develop an annual panel data set between 1930 and 1940. Using panel methods we estimate that an added dollar of federal spending in the state increased state per capita income by between 40 and 96 cents. The point estimates for nonfarm grants are higher and for AAA farm grants are much smaller and negative in some cases. The spending led to increase in durable good spending on automobiles but had no positive effects on private employment.